Initiated Chemical Vapor Deposition: A Versatile Tool for Various Device Applications. Issue 3 (30th November 2017) - Yu, Seung Jung; Pak, Kwanyong; Kwak, Moo Jin; Joo, Munkyu; Kim, Bong Jun; Oh, Myung Seok; Baek, Jieung; Park, Hongkeun; Choi, Goro; Kim, Do Heung; Choi, Junhwan; Choi, Yunho; et al.
Abstract : Advances in device technology have been accompanied by the development of new types of materials and device fabrication methods. Considering device design, initiated chemical vapor deposition (iCVD) inspires innovation as a platform technology that extends the application range of a material or device. iCVD serves as a versatile tool for surface modification using functional thin film. The building of polymeric thin films from vapor phase monomers is highly desirable for the surface modification of thermally sensitive substrates. The precise control of thin film thicknesses can be achieved using iCVD, creating a conformal coating on nano‐, and micro‐structured substrates such as membranes and microfluidics. iCVD allows for the deposition of polymer thin films of high chemical functionality, and thus, substrate surfaces can be functionalized directly from the iCVD polymer film or can selectively gain functionality through chemical reactions between functional groups on the substrate and other reactive molecules. These beneficial aspects of iCVD can spur breakthroughs in device fabrication based on the deposition of robust and functional polymer thin films. This review describes significant implications of and recent progress made in iCVD‐based technologies in three fields: electronic devices, surface engineering, and biomedical applications. Abstract : Considering device design, initiated chemical vapor deposition (iCVD) inspires innovation as a platform technology that extends the application range of a material or device. iCVD serves as a versatile tool for direct building of polymeric thin films on substrates from vapor phase monomers. This review describes significant implications of and recent progress made in iCVD‐based technologies in three fields: electronic devices, surface engineering, and biomedical applications.